New version of PUGIS - Soil information system of the Czech Republic - Adéla Marie Marhoul; Tomáš Herza; Josef Kozák; Jaroslava Janků; Jan Jehlička; Luboš Borůvka; Karel Němeček; Miroslav Jetmar; Petr Polák (Soil and Water Research)
The creation of the database system represents a complex task which is difficult to coordinate. In this work, a method of the logic framework was used for the coordination of each particular step to one integral part. In the Czech Republic, most of the information about soil was gathered within a systematic soil survey (KPP) in the period 1961-1970. Information about genetic and agronomic characteristics of agricultural soils was gathered for the whole Czech Republic. The other part of the data is coming from the databases of forest soils. This contribution is a continuation of the previous research. We are aware of the fact that in the Czech Republic exist also other soil information systems. In this work we also tried to show the practical exploitation of the large soil database. We applied many approaches to assess bulk density of the soil. It was calculated for the main soil groups and it could be applied on every soil profile in PUGIS system. We also showed different possibilities of mapping soil organic concentration or amount in soils.